Implementasi Modul AJAR sebagai Strategi Pembelajaran Pendidikan Agama Kristen di SMA Kristen Palangka Raya - Selvia Selvia; Revalina Revalina; Riky Riky; Matius Timan Herdi Ginting (Sukacita : Jurnal Pendidikan Iman Kristen, 2026)
This study's objective is to describe the implementation of teaching modules as a Christian Religious Education learning strategy at Palangka Raya Christian High School. Teaching modules are used as learning tools in the Merdeka Curriculum to help teachers design structured, contextual, and student-centered learning. Seventeen students in the tenth grade served as research subjects for this study, which employed a descriptive qualitative method. Data collection was carried out thru observation of the learning process, analysis of learning documents, and evaluation results of student learning. The study's findings show that the implementation of teaching modules is able to support the systematic implementation of learning, increase students' active participation in discussions and group activities, and help achieve fairly good assessment results. Nevertheless, some constraints were found in the implementation of learning, such as time limitations and supporting facilities. Overall, the implementation of the teaching module has positive implications for improving the quality of the Christian Religious Education learning process and outcomes, and has the potential to be developed sustainably to shape students' character based on Christian values.